A novel spaceborne photon-counting laser altimeter denoising method based on parameter-adaptive density clustering - Ren Liu; Xinming Tang; Junfeng Xie; Rujia Ma; Fan Mo; Xiaomeng Yang (GIScience & Remote Sensing)
To tackle the challenge of denoising spaceborne photon-counting laser altimeter point clouds with uneven noise density, this study proposes a denoising method based on adaptive parameter density clustering, which utilizes numerical simulations to achieve self-adaptation of key parameters (neighborhood radius [Formula: see text] and minimum number of points [Formula: see text]). First, taking the directional adaptive ellipse DBSCAN (DAE-DBSCAN) as an example, photons with different background photon count rates ([Formula: see text]) are used to traverse [Formula: see text] and [Formula: see text] to calculate their optimal values ([Formula: see text] and [Formula: see text] with the highest denoising accuracy). Then, a mathematical prediction model of [Formula: see text], [Formula: see text] and [Formula: see text] was established. The actual background photon count rates were introduced into the key parameter prediction model to obtain the optimal [Formula: see text] and [Formula: see text]. Finally, a denoising experiment was conducted using the simulated photons and the ATLAS data. The results show that the proposed method had higher accuracy than the constant parameter denoising method, with an [Formula: see text] >0.95. Even for photons of complex mountainous terrain with a high background photon count rate, the denoising accuracy was still higher than 0.9. The proposed method improves the denoising accuracy of photons with different noise densities by adapting density clustering parameters.